Characterization gravimetric do the recyclables for the Coocima hair selective collection program municipality of Caçador-SC - Campos, Roger Francisco Ferreira de; Borga, Tiago (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The environmental impact caused by solid waste has become a stalemate for both public and private. The objective of this work was to characterize physical and gravimetric composition of recyclable waste from urban and rural areas of the municipality of Caçador-SC. The study was conducted in Cooperativa Cidadania e Meio Ambiente,the period from29/07/2013 will 30/08/2013.Thetotal sample volume was 783.037 kg /month, corresponding to 447.109 kg / month in urban areas and 335.929 kg / month in the rural. The areas were divided into 9 sectors, corresponding to neighborhoods and rural lines, and performed five sampling each sector, based on the data presented paper 10.538%, 22.869% cardboard, Tetra Pack 7,647%, 3,048% Metal, Aluminum 2.961%, 9.885 Glass % Plastic Flexible 11.169%, 13.150%Hard Plastic, PET 6,862%, 2,942% Organic, Styrofoam 0.499% E 0.643%, 0.566% Lamps. Batteries 0.420%, 3.242% and reject Sanitary 3,559%. To determine thegravimetric composition of these residues was followed NBR 10007/04. From this it was possible to raise the analysis and calculation of the standard deviation, per capita generation of municipal and sample mean of each of the sectors. These data will be used in the Plan Integrated Municipal Waste Management in the Municipality of Hunter, which will impose the guidelines regarding the waste liable to recycling.